2003
DOI: 10.1037/0022-0167.50.3.351
|View full text |Cite
|
Sign up to set email alerts
|

To seek help or not to seek help: The risks of self-disclosure.

Abstract: Investigations into the reasons why people seek counseling have, for the most part, focused on approach factors, those variables that are associated with a potential client's increased likelihood of seeking psychological services. The purpose of this research, however, is to explore the role of avoidance factors, those factors that are associated with a potential client's decreased likelihood of seeking services. Across 2 studies of primarily Caucasian college students (ns ϭ 209 and 268, respectively), the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

43
397
3
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 391 publications
(463 citation statements)
references
References 38 publications
43
397
3
15
Order By: Relevance
“…help-seeking studies (see Cepeda-Benito & Short, 1998;Kelly & Achter, 1995;Vogel & Wester, 2003). The zero-order correlations also showed that attitudes were related to intent to seek help for interpersonal, drug, and academic problems.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…help-seeking studies (see Cepeda-Benito & Short, 1998;Kelly & Achter, 1995;Vogel & Wester, 2003). The zero-order correlations also showed that attitudes were related to intent to seek help for interpersonal, drug, and academic problems.…”
Section: Resultsmentioning
confidence: 88%
“…The anticipated utility and the anticipated risk of seeking help from a counselor were measured with the Disclosure Expectations Scale (DES; Vogel & Wester, 2003). The DES is an 8-item questionnaire designed to assess participants' expectations about the utility and the risks associated with talking about an emotional problem with a counselor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12] Barriers to help-seeking can include difficulties in accessing support, concerns about confidentiality and trust, a preference for informal sources of help, and stigma. 13,14 Although existing studies, including those outside of the UK, have focused on mental health help-seeking among adolescents, 10,15 university students, [16][17][18] or adults of all ages, 13,19 few have reported on the barriers experienced by young adults aged 18-25 years from the UK general population. This age group is an important cohort to study, as it is typically associated with a separation from parents and a transition into adulthood when important decisions regarding education, career, and intimate relationships are made.…”
Section: Introductionmentioning
confidence: 99%